Chemical Constituents of Plectranthus tomentosa Extract and Its Control Effect on Tetranychus kanzawai. (12th July 2022) - Sun, Yuehua; Liu, Tianlei; Sun, Cuiying; Luo, Qing
Abstract : The repellent and contact effects of Plectranthus tomentosa extracts of leaf and stem tissue on different stages of Tetranychus kanzawai were tested using the leaf-dip and insect-dip methods, and the constituents of the Plectranthus tomentosa extract were also determined. It was found that the repellent effect on Tetranychus kanzawai female adults has reached up to 84.43% after 60 min, with significant mortality of Tetranychus kanzawai at all growth stages. Sixty-nine components of the extract were identified by gas chromatography-mass spectrometry, of which limonene, followed by terpinolene, were present at the highest concentration. This research demonstrated that Plectranthus tomentosa has strong repellent and contact effects against Tetranychus kanzawai, offering potential natural strategies for the environmentally protective control of Tetranychus kanzawai in tea gardens and providing the foundation for the biomimetic synthesis of pesticides.